Safety and Feasibility of Radiotherapy Plus Camrelizumab for Locally Advanced Esophageal Squamous Cell Carcinoma. (5th June 2021) - Zhang, Wencheng; Yan, Cihui; Gao, Xuan; Li, Xiaoxia; Cao, Fuliang; Zhao, Gang; Zhao, Jingjing; Er, Puchun; Zhang, Tian; Chen, Xi; Wang, Yuwen; Jiang, Yao; et al.
Abstract: Lessons Learned: Radiotherapy plus anti–PD-1 antibody as first-line therapy is safe and feasible in locally advanced esophageal squamous cell carcinoma (ESCC). Tumor-infiltrating and peripheral lymphocytes were associated with patient survival. Further studies combining chemoradiotherapy with immunotherapy in locally advanced ESCC and exploration of predictive biomarkers are warranted. Background: We conducted a phase Ib study of radiotherapy plus programmed cell death protein 1 (PD-1) monoclonal antibody camrelizumab as first-line treatment for locally advanced esophageal squamous cell carcinoma (ESCC). Methods: We planned to enroll 20 patients with newly diagnosed locally advanced ESCC. Patients received 60 Gy radiation (2.0 Gy/fraction, 5 fractions/week), with camrelizumab (200 mg every 2 weeks) starting with radiotherapy and continuing for 32 weeks (i.e., for 16 cycles). The primary endpoints were safety and feasibility. Secondary endpoints were rates of radiologic and pathologic response, overall survival (OS), and progression-free survival (PFS). Study data were collected by the week during radiotherapy (RT), every month during the maintenance camrelizumab treatment, and every 3 months after treatment. Tumor microenvironment and peripheral blood were monitored at baseline and after 40 Gy radiation for association with efficacy. Results: Twenty patients were enrolled and received treatment. One patient (patient 10) was excluded upon discovery of a second tumor in the bladder during treatment, leaving 19 patients for analysis. Toxicity was deemed tolerable. Fourteen (74%) patients had assessed objective response. At a median follow-up time of 31.0 months (95% confidence interval [CI], 27.0–35.1), median OS and PFS times were 16.7 months (95% CI, 5.9–27.9) and 11.7 months (95% CI, 0–30.3), respectively. OS and PFS rates at 24 months were 31.6% and 35.5%, respectively. Kaplan-Meier analysis revealed associations between the following factors and OS/PFS: tumor programmed cell death ligand 1 (PD-L1) expression, PD-1 + CD8 +, PD-1 + CD4 + T cells, and PD-L1 + CD4 + T cells; peripheral blood CD4 +, CD8 +, CD4 + regulatory T cells, and their subsets. Conclusion: Radiotherapy plus camrelizumab had manageable toxicity and antitumor efficacy for locally advanced ESCC. Several biomarkers were associated with clinical benefit and deserve further study.